Spectrophotometric Analysis of Cefixime Trihydrate Tablets Using Metformin Hydrochloride as Hydrotropic Solubilizing Agent - Maheshwari, R.K.; Kinariwala, M.; Saxena, M.; Gahlot, M.; Chaki, R.; Jagwani, Y. (Asian Journal of Chemistry, 2010)
A new, simple, cost-effective, environment-friendly, safe, accurate and reproducible method was developed for quantitative analysis of cefixime trihydrate tablets. In the present investigation, 0.5 M metformin hydrochloride (an economic drug) was used as hydrotropic agent for solubilization of poorly water soluble drug cefixime trihydrate to carry out spectrophotometric analysis. The solubility of cefixime trihydrate increased to more than 18-folds. Accuracy and precision of proposed method were confirmed by recovery study. Percent recoveries estimated by proposed methods ranged from 98.33 ± 1.621 to 101.62 ± 2.002, which are very close to 100. Low values of standard deviation, percentage coefficient of variation and standard error further validated the proposed methods.